2020
DOI: 10.1101/2020.10.07.20208306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computerized Cognitive Training in Cognitively Healthy Older Adults: A Systematic Review and Network Meta-Analysis

Abstract: Background Computerized cognitive training (CCT) is a broad category of drill-and-practice interventions aims to maintain cognitive performance in older adults. Despite a supportive evidence base for general efficacy, it is unclear what types of CCT are most likely to be beneficial and what intervention design factors are essential for clinical implementation. Methods We searched MEDLINE, Embase, and PsycINFO to August 2019 for randomized controlled trials (RCTs) of any type of CCT in cognitively healthy ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 99 publications
1
29
0
2
Order By: Relevance
“…而另 一些研究则发现, 由于认知能力的提升存在天花板, 因 此相比于提升空间较大的儿童和老年人, 成年早期被 试的训练效果反而更差 [79,103] . 因此, 认知控制不同维 [77] . 前人的研究发现, 认知 训练的确可以提高不同年龄组, 包括儿童、成年早期 和老年组的认知控制水平 [89,108] , 但训练的短期效果以 及迁移能力却存在差异.…”
Section: 抑制控制能力早在儿童12个月就形成 在10~12岁unclassified
“…而另 一些研究则发现, 由于认知能力的提升存在天花板, 因 此相比于提升空间较大的儿童和老年人, 成年早期被 试的训练效果反而更差 [79,103] . 因此, 认知控制不同维 [77] . 前人的研究发现, 认知 训练的确可以提高不同年龄组, 包括儿童、成年早期 和老年组的认知控制水平 [89,108] , 但训练的短期效果以 及迁移能力却存在差异.…”
Section: 抑制控制能力早在儿童12个月就形成 在10~12岁unclassified
“…Findings from the landmark ACTIVE trial suggest that the gains in cognitive function, particularly from training that focused on speed of processing, may translate into sustained maintenance of daily functioning, reduced risk of driving cessation and reduced incidence of dementia 10 years after training (Edwards et al, 2016(Edwards et al, , 2017Rebok et al, 2014;Ross et al, 2016). Lampit et al (2014bLampit et al ( , 2020 have published the two most comprehensive reviews to date of the effectiveness of CCT trials in cognitively healthy older adults (aged ≥ 60 years). Their first meta-analysis of 51 trials indicated a small but statistically significant effect on global cognitive functioning favouring CCT over the control group (Hedges' g = 0.22, 95% confidence interval [CI] = 0.15-0.29) (Lampit et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…An update of this review included a total of 90 papers and showed similar efficacy (Hedges' g = 0.18, CI = 0.14-0.23) (Lampit et al, 2020). The majority of the trials included in these reviews were tightly controlled, group-based trials with relatively small numbers of participants (n < 50), and most employed high intensity protocols to deliver the CCT intervention, particularly in terms of the time commitment required for participants to complete the intervention (Lampit et al, 2014b(Lampit et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…There is now a solid body of evidence demonstrating e cacy of CT for improving cognition in psychiatric populations including schizophrenia [4] and major depression [5], in healthy older adults [6], and in groups at risk of developing dementia, i.e. those with mild cognitive impairment (MCI) [2,3,7,8].…”
Section: Introductionmentioning
confidence: 99%